EFEKTIFITAS PERAWATAN SMOKE DETECTOR DALAM UPAYA MITIGASI KEBAKARAN DI KM. TILONGKABILA - Cindy May Syafitri; Rizal Rochmansyah; Mashartanto, Achmad Ali; Putra, Riki Wanda; N.H, Meilinasari (STKIP Subang, 2026)
“The Effectiveness of Smoke Detector Maintenance in Fire Mitigation Efforts on Board KM Tilongkabila,” supervised by Mr. Rizal Rochmansyah, S.Tr.Pel., M.Tr.T., and Mr. Riki Wanda Putra, M.Pd. This study aims to analyze the effectiveness of smoke detector maintenance in supporting fire mitigation efforts on board KM Tilongkabila. The research employed a descriptive qualitative approach, with data collected through field observations, semi-structured interviews with four key informants (the Captain, Second Engineer, Third Officer, and Radio Officer), and documentation review. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing, strengthened by source and technique triangulation. The results indicate that smoke detector maintenance has been carried out routinely through monthly inspections, sensor cleaning, alarm testing, and documentation in the logbook. The alarm system is integrated with the bridge panel and the ship’s internal communication system, and is supported by regular fire drills. The main challenges identified include dust and humidity in the engine room, which may trigger false alarms. Overall, smoke detector maintenance is considered effective in supporting early fire mitigation; however, improvements are still needed in terms of sensor modernization and environmental control.